PENGAKUAN PENYUSUTAN ASET TETAP MENURUT PERPAJAKAN DAN PENGARUHNYA TERHADAP LABA PERUSAHAAN PADA PT SEMEN TONASA (Persero) - adriani adriani; Bakri Bakri; Andi Muh Sofian Assaury Yahya (STIM LASHARAN JAYA MAKASSAR, 2022)
Revisions to tax laws have been repeatedly made, especially income tax No. 07 of 1994, the last of which was changed to Law No. 36 of 2008 which requires companies to prepare fiscal financial statements to determine taxable profit. One indicator that can affect the company's profit is the depreciation expense in this case the depreciation expense can be a deduction factor from the taxable profit. the use of the depreciation method is very important in this case, especially PT Semen Tonasa which is engaged in industry, the purpose of this study is whether the use of the depreciation method carried out by PT cementonasa is appropriate as a deduction from taxable profit to meet the provisions of law No. 36 of 2008 and the second purpose is whether the provisions of law no. 36 of 2008 as the basis for taxation provisions in determining taxable profit can affect the tax calculation basis of PT Semen Tonasa. The sources of data in this study are the financial statements of PT Semen Tonasa for the last 3 years, a list of assets and amortization report of PT Semen Tonasa's assets and the calculation of the income tax of PT Semen Tonasa. The data analysis technique used in this study uses the Miles and Huberman data analysis technique which in the process uses the theory and tax calculation tools applicable to the Income Tax Law Article 11 paragraph (1) The results showed the use of the method in calculating the amortization of assets at PT Semen Tonasa using the straight-line method, the use of the amortization method used (the straight-line method) became an effective tool for measuring asset activity so that the company's profit reduction factor became more precise and could meet the laws and regulations. invitation No. 36 of 2008.